The impact of trade liberalisation on market concentration - Zhu, Hengxi (2023)
In this empirical study, we use the Difference in Difference estimation to investigate the impact of trade liberalisation on market concentration. We include different measures of market concentration to examine the effect of trade liberalisation on different firm levels (e.g., HHI, CR20, CR4, etc.). We employed the Annual Surveyed Industrial Enterprise (ASIE) firm-industry level dataset to compute the market concentration. Our findings show that output tariff reduction has a significant positive impact on market concentration. This result is robust at all levels of market concentration measures. Then, we found that under trade liberalisation, rising market concentration is mainly driven by the decreasing number of firms.